ANALISIS KREDIT MACET (PT. BANK SULUT, TBK DI MANADO) - Fransisca Claudya Mewoh; Harry J Sumampouw; Lucky F Tamengkel F Tamengkel (Universitas Sam Ratulangi, 2016)
This study is based on that: The extension of credit by the bank must pay attention to the principles of sound lending. To gain confidence, such as the explanation of Article 8 of Law No. 10 of 1998 on banking, namely: